2020
DOI: 10.1186/s12889-020-8453-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitudes and practice towards Vitamin D among university students in Pakistan

Abstract: Background: Pakistan has one of the highest reported incidence of vitamin D deficiency in studies conducted worldwide. However, there has been very limited exploration of vitamin D related knowledge, attitudes and practices among healthy youth in Pakistan. Methods: A cross-sectional survey was conducted among youth (aged > 16 years) from two engineering universities in Pakistan. Participants were asked questions on their concern about vitamin D levels, testing, and supplementation practices. Knowledge was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
24
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 38 publications
7
24
2
3
Order By: Relevance
“…Deschasaux et al reported that, at least in Europe, people are often confused about the sources as well as health effects of vitamin D (2016). Similar observations were also reported in other studies from different countries (Boland et al, 2015;O'Connor, Glatt, White, & Revuelta Iniesta, 2018;Özel, Cantarero-Arevalo, & Jacobsen, 2020;Tariq, Khan, & Basharat, 2020). Physicians and the media were identified as key information providers on this topic, and it was suggested that health professionals should also be better informed about the health effects of vitamin D, and particularly about the vitamin D deficiency risk factors (Deschasaux et al, 2016).…”
Section: Introductionsupporting
confidence: 70%
“…Deschasaux et al reported that, at least in Europe, people are often confused about the sources as well as health effects of vitamin D (2016). Similar observations were also reported in other studies from different countries (Boland et al, 2015;O'Connor, Glatt, White, & Revuelta Iniesta, 2018;Özel, Cantarero-Arevalo, & Jacobsen, 2020;Tariq, Khan, & Basharat, 2020). Physicians and the media were identified as key information providers on this topic, and it was suggested that health professionals should also be better informed about the health effects of vitamin D, and particularly about the vitamin D deficiency risk factors (Deschasaux et al, 2016).…”
Section: Introductionsupporting
confidence: 70%
“…18 In a Canadian study, only 26% of participants identified the sources of vitamin D 19 , and only 17% recognized sources of vitamin D other than sun in a study conducted on a group of New Zealand athletes. 20 Age had an impact on participant's knowledge score about vitamin D sources.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, negative attitude towards sunlight exposure can be a big challenge in SA. It has been reported that lack of knowledge about vitamin D and negative attitude towards sunlight exposure is prevalent among Indian and Pakistani students [108,109]. This lack of knowledge and negative attitude could be a key reason behind staying away from sunlight which can contribute to reduce serum vitamin D level.…”
Section: Discussionmentioning
confidence: 99%